Ashy dermatosis with involvement of mucous membranes - Margarida Rato; Ana Filipe Monteiro; João Aranha; Ermelindo Tavares (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Ashy dermatosis is a rare condition, of unknown aetiology, in which mucous membranes are typically spared. The authors report the case of a 57-year-old female with a history of asymptomatic gray-bluish macules located on the trunk and oral mucosa. There were no relief changes on examination. Skin biopsies from the oral mucosa and trunk were performed and both were compatible with ashy dermatosis. The patient started treatment with oral clofazimine but due to the absence of clinical improvement the drug was discontinued three months later. This case report illustrates an atypical case of ashy dermatosis owing to the involvement of mucous membranes, which is rarely described in the literature.